GAMBARAN STATUS GIZI PADA SISWA SEKOLAH DASAR KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI - Yunita Aria Ningsih; Suyanto "; Tuti Restuastuti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTNutrition is one of the important factors that determine the level of health and harmony between physical and mental development. During development of the child, nutritional adequacy is absolute thing that must always be considered by parent. School children in general are in a period of very rapid growth, that nutrition plays an important role in the development of the child. The aim of this study was to describe the nutritional status of elementary school students in the district Rangsang Kepulauan Meranti, so that further action can be done if it is found that if the nutrition problem requires intervention by the parties concerned. This is a descriptive study using cluster sampling method which number of samples obtained are 210 people who carried out the calculation of BMI by measuring height and weight. Retrieving data using anthropometric methods based on the table KEPMENKES No. 1995 / Menkes / SK / XII / 2010 on Standards Anthropometric Assessment Nutritional Status of Children with BMI per age, then the nutritional status divided into malnutrition, underweight, normal, overweight and obese. The results obtained normal nutritional status as the highest value are 151 (71.9%), nutritional status of underweight are 26 people (12.4%), nutritional status is malnutrition are 13 people (6.2%), nutritional status overweight are 13 people (6.2%) and obesity nutritional status of 7 people (3.3%).Keywords: nutrition, nutritional status, primary school children